2021
DOI: 10.1002/mar.21449
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Berlyne's inverted U‐shape relationship between complexity and liking: The role of effort, arousal, and status in the appreciation of product design aesthetics

Abstract: A common assumption in the psychology of aesthetics is that there exists an inverted U‐shape relationship between complexity and liking due to two countervailing effects of increasing complexity, namely a negative effect of cognitive effort and a positive effect of arousal or interest. In the context of product design, several studies with over 1800 participants in total showed that aesthetic complexity does influence consumer appraisals, but there was scant evidence for an inverted U‐shape relationship. Regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
(84 reference statements)
0
17
0
Order By: Relevance
“…This study found that including humor had an indirect persuasive effect on message sidedness through the reduction of negative cognitions. Velde and colleagues hypothesized an indirect effect through negative affect in line with arousal theory (Althuizen, 2021; Berlyne, 1960, 1971) but could not find any such effect. They thus suggested the need for further research.…”
Section: Theoretical Backgroundmentioning
confidence: 98%
See 1 more Smart Citation
“…This study found that including humor had an indirect persuasive effect on message sidedness through the reduction of negative cognitions. Velde and colleagues hypothesized an indirect effect through negative affect in line with arousal theory (Althuizen, 2021; Berlyne, 1960, 1971) but could not find any such effect. They thus suggested the need for further research.…”
Section: Theoretical Backgroundmentioning
confidence: 98%
“…Both humor research (e.g., Yoon, 2018) and research on two-sided persuasion (e.g., Cornelis et al, 2013) have put forward the same affective mechanism and effect, which are based on arousal theory F I G U R E 1 Conceptual framework and design of the three studies (Althuizen, 2021;Berlyne, 1960Berlyne, , 1971. This theory is therefore appropriate to explain the affective mechanisms of humor in two-sided advertising.…”
Section: The Mediating Effect Of Surprisementioning
confidence: 99%
“…However, research on disfluency has not examined an affective mechanism that motivates consumers to approach or favor disfluency. Recent research in psychology has suggested that perceived novelty is a key antecedent of the feeling‐of‐interest (Althuizen, 2021; Silvia, 2005). Interest is an evolutionarily adaptive emotion that motivates people to approach new information and experiences (Izard, 2007).…”
Section: Review Of Relevant Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Processing fluency (holistic information processing) and visual complexity Visual processing fluency or complexity is dependent on the number of components a product has, the interactions among them, and the level of the PD novelty they project (Kumar and Noble, 2016;Orth and Wirtz, 2014). Studies have indicated that processing fluency increases a product's attractiveness and positively affects consumer preferences and responses (van Rompay and Pruyn, 2011;Landwehr et al, 2013;Althuizen, 2021). This conclusion is based on conceptual and perceptual fluency/complexity theories that postulate design can conceptually (through the design's meaning) and perceptually (through the visual elements of design) influence consumers' recognition of, categorisation of, and opinion about the product (Shapiro, 1999;Miceli et al, 2014).…”
Section: Link 2: Theories Related To Product Design and Consumer Resp...mentioning
confidence: 99%